A formação profissionalizante no Centro de Educação Integrada Professor Eliseu Viana sob as diretrizes da Lei Nº 5.692/1971, Mossoró/RN - Bandeira, Tainá da Silva (2020)
This work aims to analyze the professional training offered by the Professor Eliseu Viana Integrated Education Center (CEIPEV) under the guidelines of Law nº 5.692 / 1971. This legislation was implemented during the period in which Brazil was experiencing the height of the civil-military dictatorship (1964-1985) and was one of the greatest educational reforms of this historic moment. The law changed the existing educational structure for the first and second grades, together with that last grade, compulsory vocational training. CEIPEV was one of the first three reform experiences in Rio Grande do Norte, being the model institution in Mossoró and region. He started high school in the academic year of 1973, offering courses in Accounting, Nursing and Agriculture. We started with the reflection on the macrostructure of the analyzed teaching, the political, economic and educational contexts, and we entered the school with the analyzes about the offered training, thus determining the chaining of the chapters: starting the discussion about the contexts, reflecting the legislation and culminating in the analysis of the vocational training offered by the school. As for the theoretical contribution, we have three key concepts that permeate all analysis: work, training and duality. The analysis categories are: school culture - based on the study by Julia (2001) - and memory - Halbwachs (2015) -, which allowed investigating the following sources: printed and digitalized newspapers, documents from private archives, interviews with educational agents and alumni and documents produced by the institution. We conclude that CEIPEV offered education for work in line with the legislation and, its first classes, managed to implement the guidelines put in place, but, not fully and, thus, gradually began to suffer from the lack of investments falling short of what was expected and spoken. In addition, the interests of ascending to Higher Education caused the disinterest of students who escaped to other institutions, changing the configuration of students served by the institution. Finally, the arrival of another vocational school, better equipped, made CEIPEV's situation sensitive. However, even though CEIPEV's professional training was not fully attended, it contemplated the law's ideological basis, human capital, serving only the interests of the economic market and distancing this teaching from an omnilateral emancipatory training.